2020
DOI: 10.3390/s20030741
|View full text |Cite
|
Sign up to set email alerts
|

A Refractive Index Sensor Based on H-Shaped Photonic Crystal Fibers Coated with Ag-Graphene Layers

Abstract: An Ag-graphene layers-coated H-shaped photonic crystal fiber (PCF) surface plasmon resonance (SPR) sensor with a U-shaped grooves open structure for refractive index (RI) sensing is proposed and numerically simulated by the finite element method (FEM). The designed sensor could solve the problems of air-holes material coating and analyte filling in PCF. Two big air-holes in the x-axis produce a birefringence phenomenon leading to the confinement loss and sensitivity of x-polarized light being much stronger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 31 publications
1
41
0
1
Order By: Relevance
“…Li et al reported a H-shaped PCF [ 1 ] coated with Ag-graphene layers. The open U-shaped groove structure simplifies the preparation process of the material layer.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al reported a H-shaped PCF [ 1 ] coated with Ag-graphene layers. The open U-shaped groove structure simplifies the preparation process of the material layer.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…With the development of high technology, many effective optical fiber sensing technologies for detecting refractive index have been proposed so far, such as fiber grating and fiber interferometer. Surface plasmon resonance (SPR) is widely used because of its high sensitivity [ 1 ], high resolution [ 2 ], strong selectivity, wide working wavelength range and other [ 3 ] advantages, especially in gas detection, food safety [ 4 ], biosensor, chemical detection [ 5 , 6 ], environmental monitoring and control, medical [ 7 ] and other fields. There are still some problems for all kinds of common optical fiber SPR sensors, such as mode coupling and complex operation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the fitting curve, in this refractive index range there are two slopes which indicate the sensitivity of the biosensor. The first sensitivity was 2770 nm/RIU in the refractive index range from 1.33 to 1.36, and the second sensitivity was 6057 nm/RIU in the refractive index range from 1.36 to 1.41 [ 59 ].…”
Section: Graphene-based Fiber Coupled Spr Biosensormentioning
confidence: 99%
“… ( a ) Schematic of the designed Ag–Graphene coated photonic crystal fiber (PCF)–SPR sensor. ( b ) The relationship between the resonant wavelength and the analyte’s refractive index varies from 1.33 to 1.41 (adapted with permission from Reference [ 59 ], copyright MDPI). …”
Section: Figurementioning
confidence: 99%
“…When the RI was from 1.40 to 1.43, the sensor had a high linear sensitivity of 3978 nm/RIU. Li et al [ 13 ] recently obtained an H-type PCF surface plasmon resonance sensor that was coated with an Ag-graphene layer. In the linear RI sensing area of 1.33–1.36, this sensor had an average wavelength sensitivity of 2770 nm/RIU and a resolution of 3.61 × 10 −5 RIU.…”
Section: Introductionmentioning
confidence: 99%